A Socio-Political Study of Autobiography “Bajang Aamad“ - Tauheed, Irfan; Iqbal, Saima; Kausar, Amina (sourcecoder, 2022)
Colonel Muhammad Khan (1910-1999) is one of the renowned writers of Urdu literature. His unique style of writing has earned him a distinctive status. The author's socio-political consciousness is read in full swing in his autobiography “Bajang Aamad” & presents the domestic and international socio-political landscape in an unbiased manner. As you study the journal, the reader begins to discover many facts of the past. The author has elaborated the political and social tensions of India and the Middle East. The writer uses his God-given ability to narrate the events and observations that took place during his military service in the past in a very captivating way. That is why, the reader cannot help but be impressed by his autobiography. The author has made his autobiography interesting by using distortions, alterations of words, a coherent style of narration of events, rhymes and proverbs.